The Impact of Participation in Intercollegiate Athletics on Income and Graduation - Long, James E.; Caudill, Steven B. (The Review of Economics and Statistics, 1991)
Males who participated in intercollegiate athletics are estimated to receive 4 percent higher annual incomes than similar nonathletes. No such income premium associated with college athletics is revealed among females. Both male and female athletes who attended colleges and universities in the early 1970s had higher graduation rates than other students. Since the models used to estimate income and graduation differentials included many measurable determinants of labor market and academic outcomes, these findings suggest that athletic participation may enhance the development of discipline, confidence, motivation, a competitive spirit, or other subjective traits that encourage success. Copyright 1991 by MIT Press.